Commode Cardia—Death by Valsalva Maneuver: A Case Series1. Issue 6 (22nd September 2016) - Fisher‐Hubbard, Amanda O.; Kesha, Kilak; Diaz, Francisco; Njiwaji, Chantel; Chi, PaoLin; Schmidt, Carl J.
Abstract: The Valsalva maneuver is used in clinical medicine for the diagnosis and/or treatment of various cardiovascular conditions. It can also be used in activities of daily living, such as defecation. Due to the cardiovascular effects produced during the Valsalva maneuver, it may be contraindicated in certain medical conditions and could be a trigger of sudden cardiac death. The incidence and prevalence of death following Valsalva maneuver in the presence of underlying cardiovascular disease, or "commode cardia, " has not been examined. In 2012, the Wayne County Medical Examiner's Office (Detroit, MI) investigated 21 deaths that occurred on the toilet, fourteen of which were due to cardiovascular disease. In another 31 deaths in the bathroom due to cardiovascular disease, the possibility that the decedent defecated immediately prior to death could not be excluded. Hence, the incidence of commode cardia in this population ranges from 2.3 to 7.4% of all cardiovascular‐related deaths.